Wool is a knitted fabric that itches, isn't it?. Issue 1 (1st October 2014) - Hebrok, Marie; Klepp, Ingun Grimstad
In this article we explore in what ways consumers preconceptions of wool influence their ability to recognize it as a fabric. Do we know that it is wool because it itches, or, conversely, does it itch because we think that it is wool? The analysis builds on three different methods; wardrobe studies, sample tests and interviews, in order to explore both informants' visual senses, and also applied tactile senses. It aims to bring together social science and textile technology methodologies and understanding in order to understand the properties of wool. It does this through adopting a multisensory understanding of the material. The research aimed to explore the associations with and experiences of wearing wool. This, we argue is as important as the senses in the process of identifying woollen fibres. The research found that the strongest influences in fabric identification were: perceptions of use, fabric type and fibres, colour, structure patterns and the 'feel' of the fabric.